KEMAMPUAN EMPAT JENIS TANAMAN DALAM MENYERAP CEMARAN MERKURI DI MEDIA TAILING - Linda, Mardekawati; hanudin, Bur; Iswan, Dewantara (Universitas Tanjungpura, 2013)
This study aims to determine the level of absorption mercury contamination in plants and would like to know which plants are best at absorbing mercury contamination in tailings. plants used were Casuarina junghuniana, Cinnamomum porrectum (Roxb.), Melastoma affine and Dillenia suffruticosa Griff ex Hook. This study uses RCD (randomized completely design) with 8 treatments on plants and each treatment was repeated 5 times. The analysis showed that the Casuarina junghuniana, Cinnamomum porrectum (Roxb.), Melastoma affine and Dillenia suffruticosa Griff ex Hook has the ability to absorb mercury contamination in tailing and the tolerance to mercury contamination. The results showed that the higher the growth rate, the higher the mercury is absorbed in plant tissues. The best types of plants to absorb mercury contamination is Melastoma affine and Dillenia suffruticosa Griff ex Hook because this plant is a plant that tolerance and is a pioneer plant that can grow in soil that has a low nutrient content, has rapid growth and are able to grow in the open and logged over . The analysis showed that the levels of mercury in the tissues of plants and media higher than 0.02 ppm. However, the levels of mercury in the media on the treatment of P3, P5, P6, and P7 contains mercury <0.02 ppm. Keywords : Casuarina junghuniana, Cinnamomum porrectum (Roxb.), Melastoma affine and Dillenia suffruticosa Griff ex Hook, Phytoremediation and Tailings.